PENGARUH IMPLEMENTASI SYARIAH GOVERNANCE TERHADAP LOYALITAS NASABAH (Studi Kasus Perbankan Syariah Yang Terdaftar Di Kota Malang) - Rukmiati Rumadan; Noor Shodiq Askandar; Mohammad Amin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThis research was conducted to analyze the effect of Sharia governanceimplementation on customer loyalty. The population in this study is all customersof Islamic Banks registered in the city of Malang. based on the sample criteriathat have been established there are 7 Sharia Banks that are the researchsamples. Sampling in this study was carried out by giving questionnaires to thenevaluate the answers of the respondents. The analytical method used in this studyis Multiple Linear Regression with analysis using SPSS for Windows v20. basedon the results of testing hypotheses that have been done, then the results of thestudy Simultaneously Transparency, Accountability, Responsibility,Independence, Justice and Sharia Compliance affect the banking customer loyaltyin the city of Malang. Partial test results show that Transparency has no effect oncustomer loyalty while Accountability, Responsibility, Independence, Justice andSharia Compliance affect the banking customer Loyalty in the city of Malang.Keyword: Transparency, Accountability, Responsibility, Independence,Justice and Sharia Compliance, Customer Loyalty.